An Experimental Study on the Use Of Interactive Flipbook Media to Improve Students’ Learning Motivation - Andreas, Mentari; Fitrawati, Fitrawati; Tiarina, Yuli (Widyagogik, 2025)
The combination of digital learning media has become increasingly important in enhancing students’ motivation and engagement in educational settings. One digital medium that has gained considerable attention is interactive flipbook media, which combines text, images, animations, videos, and interactive features to support active learning. This study aims to systematically review empirical research examining the impact of interactive flipbook media on students’ learning motivation. Following the PRISMA 2020 guidelines, a systematic literature review was conducted using Google Scholar and ERIC databases. Studies published between 2015 and 2025 were screened based on predefined inclusion and exclusion criteria, resulting in 26 eligible empirical articles. The findings reveal five themes: The positive impact of interactive flipbook media on students’ intrinsic motivation, Its influence on extrinsic motivation, Increased student participation in classroom activities, The superiority of flipbook media compared to conventional teaching methods, and Key factors enhancing students’ learning enthusiasm, including visual appeal, interactivity, cultural relevance, and integration with active learning models. Overall, the results indicate that interactive flipbook media is an effective instructional tool for improving students’ learning motivation and engagement across various educational levels. These findings suggest that educators are encouraged to integrate interactive flipbooks into teaching practices to create more engaging and motivating learning environments